Astronaut Annie - Slade, Suzanne (Tilbury House Publishers, 2018)
When Annie has a career day at her school, each member of her family wonders if she will choose their career path--her grandfather the news photographer, her father the mountain climber or her mother the basketball player--until she reveals a dream that is all her own.